Actor-based management and captive shared services: a model for creative governance in the SME sector? - Seal, Will; Herbert, Ian (Proceedings of Pragmatic Constructivism, 2013)
This paper was presented at the 3rd Actor-reality conference, Aarhus University, October 23-25, 2013.